Kynurenic acid inhibits the electrical stimulation induced elevated pituitary adenylate cyclase-activating polypeptide expression in the TNC - Körtési Tamás; Tuka Bernadett; Tajti János; Bagoly Teréz; Fülöp Ferenc; Helyes Zsuzsanna; Vécsei László (2018)
Background: Migraine is a primary headache of imprecisely known mechanism, but activation of the trigeminovascular system (TS) appears to be essential during the attack. Intensive research has recently focused on pituitary adenylate cyclase-activating polypeptide (PACAP) and the kynurenine systems as potential pathogenic factors. Aim: We investigated the link between these important mediators and the effects of kynurenic acid (KYNA) and its synthetic analog (KYNA-a) on PACAP expression in the rat trigeminal nucleus caudalis (TNC) in a TS stimulation model related to migraine mechanisms. Methods: Adult male Sprague-Dawley rats were pretreated with KYNA, KYNA-a, the NMDA receptor antagonist MK-801, or saline (vehicle). Next, the trigeminal ganglion (TRG) was electrically stimulated, the animals were transcardially perfused following 180 min, and the TNC was removed. In the TNC samples, 38 amino acid form of PACAP (PACAP(1-38))-like radioimmunoactivity was measured by radioimmunoassay, the relative optical density of preproPACAP was assessed by Western blot analysis, and PACAP(1-38) mRNA was detected by real-time PCR. Results and conclusion: Electrical TRG stimulation resulted in significant increases of PACAP(1-38)-LI, preproPACAP, and PACAP(1-38) mRNA in the TNC. These increases were prevented by the pretreatments with KYNA, KYNA-a, and MK-801. This is the first study to provide evidence for a direct link between PACAP and the kynurenine system during TS activation.